The amphioxus genome provides unique insight into the evolution of immunity - Dishaw, Larry J. (Oxford University Press, 2012)
Immune systems evolve as essential strategies to maintain homeostasis with the environment, prevent microbial assault and recycle damaged host tissues. The immune system is composed of two components, innate and adaptive immunity. The former is common to all animals while the latter consists of a vertebrate-specific system that relies on somatically derived lymphocytes and is associated with near limitless genetic diversity as well as long-term memory. Deuterostome invertebrates provide a view of immune repertoires in phyla that immediately predate the origins of vertebrates. Genomic studies in amphioxus, a cephalochordate, have revealed homologs of genes encoding most innate immune receptors found in vertebrates; however, many of the gene families have undergone dramatic expansions, greatly increasing the innate immune repertoire. In addition, domain-swapping accounts for the innovation of new predicted pathways of receptor function. In both amphioxus and Ciona, a urochordate, the VCBPs (variable region containing chitin-binding proteins), which consist of immunoglobulin V (variable) and chitin binding domains, mediate recognition through the V domains. The V domains of VCBPs in amphioxus exhibit high levels of allelic complexity that presumably relate to functional specificity. Various features of the amphioxus immune repertoire reflect novel selective pressures, which likely have resulted in innovative strategies. Functional genomic studies underscore the value of amphioxus as a model for studying innate immunity and may help reveal how unique relationships between innate immune receptors and both pathogens and symbionts factored in the evolution of adaptive immune systems.